2018
DOI: 10.1136/bmjsem-2018-000368
|View full text |Cite
|
Sign up to set email alerts
|

Impact of active and passive social facilitation on self-paced endurance and sprint exercise: encouragement augments performance and motivation to exercise

Abstract: ObjectiveThe positive effect of an audience on performance is anecdotally well known, but the impact of such social facilitation to both performance and the motivation to exercise have not been thoroughly explored. The aim of this study was therefore to investigate verbal encouragement as a means to promote positive behavioural adherence to exercise and augmented performance.MethodsTwelve untrained but active individuals (seven female), age 24±3 years participated in this study. Exercise conditions with extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 23 publications
2
42
1
3
Order By: Relevance
“…In an examination of both short-distance and long-distance running, it was found that active social facilitation caused a significant difference in subject performance in running trials, via experimentation conducted on untrained but active individuals (Edwards et al, 2018). Verbal encouragement was found to bolster the performance of the subjects in both endurance and sprint exercises, suggesting the positive impact of active social facilitation on running of those who are not competitive runners (Edwards et al, 2018).…”
Section: Social Facilitation and Runningmentioning
confidence: 99%
See 2 more Smart Citations
“…In an examination of both short-distance and long-distance running, it was found that active social facilitation caused a significant difference in subject performance in running trials, via experimentation conducted on untrained but active individuals (Edwards et al, 2018). Verbal encouragement was found to bolster the performance of the subjects in both endurance and sprint exercises, suggesting the positive impact of active social facilitation on running of those who are not competitive runners (Edwards et al, 2018).…”
Section: Social Facilitation and Runningmentioning
confidence: 99%
“…Students who did not participate in a sport were expected to be most impacted by social facilitation, as it was believed that their lack of sports activity would cause their inability to control their pace following the introduction of a facilitator. This hypothesis was created as a result of past conclusions on social facilitation, which showed statistically significant improvements in ability while one was in the presence of others and while completing tasks of familiarity (Strube, 2005;Allport, 1924Allport, /1975Zajonc, 1965;Edwards et al, 2018).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying either an athlete's perception of the importance, probability or controllability of successfully achieving the goal of a task, will thus modify pacing behavior through increased or decreased motivation (Rhoden et al, 2015 ; Wolff et al, 2019 ). Factors such as false or deceptive feedback (Williams et al, 2014 ), encouragements (Edwards et al, 2018 ), racing an opponent (Konings et al, 2016 ), modifying the salience of the reward or the probability of attaining a given goal (e.g., to be close to one's personal best, to be close to a top-3 ranking or qualification) (Schiphof-Godart et al, 2018 ) can enhance performance through by adapting pacing behavior. All of these factors modify either the weight of the “costs” of the task or the “reward” of reaching the set goal, hence increasing or decreasing athletes' motivation to exert effort (Schiphof-Godart et al, 2018 ).…”
Section: Coaching Pacing Behavior Of Youth Athletes: Motivation and Tmentioning
confidence: 99%
“…It is not exclusively familiar peers who may impact an athlete's performance, as recent research has shown how for example basketball players performance are affected by sheer audience size (Böheim et al, 2019). This effect has also been shown when bench spotters are present (Sheridan et al, 2019), presence of verbally active peers in cycling tests (Edwards et al, 2018) and when in company of other competitors (Hibbert et al, 2018). In other words, the present audience may play a partial but significant role in the fighter's performance.…”
Section: Introductionmentioning
confidence: 99%